POSSIBILITIES OF ASSESSING THE ATTENTION AND VISUAL MEMORY IN PRIMARY SCHOOL CHILDREN (GYMNASIUM, 2017)
The attention disorders characterized by diminishing abilities such as perception, thinking, unbalance the children's daily life. The disorders appear as difficulty in concentrating, impulsiveness, and sometimes hyperactivity. Absent minded, unfocused, often agitated, the children can't have continuity in their thoughts and projects. Their intelligence is good, but wrongly used, and their memory is used very little. This study wanted to bring to forefront this particular theme because the mental processes such as attention and memory play an important role in the children's academic results. An increasing number of teachers observed lately a lack of focus in children during classes, and in many of the situations there is no answer when it comes to a correct conduct, many times this leading to unsatisfying academic results.